The Effectiveness of Cognitive-Behavioral Group Therapy on Improving Quality of Life and Increasing CD4+ Lymphocytes Count in HIV/AIDS Patients in Ahvaz - Shahla Molavi; Naser Seraj-Khorrami; Parvin Ehteshamzadeh; Mehdi Sayyahbargard (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: HIV/AIDS is a community medicine issue and has a wide range of negative consequences and challenges. This research aimed to investigate the effect of cognitive-behavioral group therapy on improving the quality of life and increasing CD4+ lymphocyte count in HIV/AIDS patients. Materials and Methods: The present study was a quasi-experimental study with pre-test and post-test design and control group. The statistical population included HIV/AIDS patients in Ahvaz Behavioral Counseling Center who were selected by simple random sampling method. The sample consisted of 30 patients who were randomly assigned to two groups of cognitive-behavioral therapy and control group. After implementing pre-test on the cognitive-behavioral and control groups, the experimental intervention was administered in 8 sessions for one hour and a half as one session per week for experimental group. Quality of Life Scale, CD4 Index and Demographic Factor Questionnaire were used for data collection. Multivariate analysis of covariance with SPSS software version 22 was used for data analysis. Results: The results showed that in the experimental group that received cognitive-behavioral therapy, the mean (SD) quality of life score increased from 166.9 (26.7) in the pre-test to 199.5 (21.4) in the post-test (P<0.001) but in control group, the mean (SD) varied from 167.8 (25.5) in pre-test to 168.2 (18.3) in post-test, which was not significant. Also, the mean (SD) of the CD4+ lymphocyte count in the experimental group increased from 247.8 (65.1) in the pre-test to 341.8 (71.1) in the post-test (P<0.001); however, the mean (SD) count in the control group varied from 254.2 (46.2) in the pre-test reached to 256.26 (56.8) in the post-test which was not significant. Conclusion: It can be concluded that cognitive-behavioral therapy improved the quality of life and CD4+ lymphocyte count in HIV/AIDS patients. DOI: http://doi.org/10.22037/ch.v7i2.28031